2019
DOI: 10.1016/j.ymthe.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-Based Protein Replacement Therapy for the Heart

Abstract: Myocardial infarction (MI) and heart failure (HF) are the leading causes of death in the United States and in most other industrialized nations. MI leads to a massive loss of cardiomyocytes (CMs), which are replaced with non-CM cells, leading to scarring and, in most cases, HF. The adult mammalian heart has a low intrinsic regenerative capacity, mainly because of cell-cycle arrest in CMs. No effective treatment promoting heart regeneration is currently available. Recent efforts to use DNA-based or viral gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 65 publications
1
92
0
Order By: Relevance
“…Protein replacement therapies based on IVT mRNA have been mainly directed to the liver [201], lungs [202], and heart [203] because of the accessibility of these organs. However, other organs and tissues, such as skin [204], back of the eye [205] or nasal cavity [131] have also been evaluated as target sites.…”
Section: Protein Replacementmentioning
confidence: 99%
“…Protein replacement therapies based on IVT mRNA have been mainly directed to the liver [201], lungs [202], and heart [203] because of the accessibility of these organs. However, other organs and tissues, such as skin [204], back of the eye [205] or nasal cavity [131] have also been evaluated as target sites.…”
Section: Protein Replacementmentioning
confidence: 99%
“…Our growing understanding of the functionality of 5′ caps and the consequences of disrupting cap‐dependent biochemical processes that result in severe medical disorders make 5′ caps attractive for the development of novel pharmaceutic and therapeutic approaches . Potential applications for cap analogues are foreseeable in antiviral therapy, cancer treatment (including eIF4E targeting and mRNA‐based immunotherapy), spinal muscular atrophy treatment, and treatment of genetic diseases by mRNA‐based protein replacement therapy . Essential for the success of RNA‐based therapeutics is the development of methods to introduce mRNA into cells and the improvement of stability and translation efficiency of the therapeutic RNA itself .…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications for cap analogues are foreseeable in antiviral therapy, cancer treatment (including eIF4E targeting and mRNA‐based immunotherapy), spinal muscular atrophy treatment, and treatment of genetic diseases by mRNA‐based protein replacement therapy . Essential for the success of RNA‐based therapeutics is the development of methods to introduce mRNA into cells and the improvement of stability and translation efficiency of the therapeutic RNA itself . The high potential of mRNA‐cap‐based approaches has been demonstrated in the first application of 5′‐capped RNAs in preclinical studies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing mRNA into the heart, however, has proven to be very challenging. Despite the difficulties, several preclinical studies have shown regeneration of cardiac tissue using a variety of IVT mRNA, as illustrated in the review by Magadum et al 6 Augmenting vascularization of the infarcted heart using mRNA is now under clinical evaluation. Another promising area of IVT mRNA application is in the field of monoclonal antibodies, which is now one of the fastest growing pharmaceutical sectors in the market.…”
mentioning
confidence: 99%